Kirigami-inspired, highly stretchable micro-supercapacitor patches fabricated by laser conversion and cutting. (December 2018) - Xu, Renxiao; Zverev, Anton; Hung, Aaron; Shen, Caiwei; Irie, Lauren; Ding, Geoffrey; Whitmeyer, Michael; Ren, Liangjie; Griffin, Brandon; Melcher, Jack; Zheng, Lily; Zang, Xining; et al.
Abstract The recent developments in material sciences and rational structural designs have advanced the field of compliant and deformable electronics systems. However, many of these systems are limited in either overall stretchability or areal coverage of functional components. Here, we design a construct inspired by Kirigami for highly deformable micro-supercapacitor patches with high areal coverages of electrode and electrolyte materials. These patches can be fabricated in simple and efficient steps by laser-assisted graphitic conversion and cutting. Because the Kirigami cuts significantly increase structural compliance, segments in the patches can buckle, rotate, bend and twist to accommodate large overall deformations with only a small strain (<3%) in active electrode areas. Electrochemical testing results have proved that electrical and electrochemical performances are preserved under large deformation, with less than 2% change in capacitance when the patch is elongated to 382.5% of its initial length. The high design flexibility can enable various types of electrical connections among an array of supercapacitors residing in one patch, by using different Kirigami designs. Supercapacitors: Large-area flexibility Kirigami-inspired "cuts" enable the fabrication of flexible micro-supercapacitors with large-area coverage of the functional component. Flexible electronic devices typically rely on non-flexible—or even brittle—hard functional materials; flexibility is achieved by limiting the areal coverage of the functional component, but this can harm performance. Kirigami—introducing cuts to enable a range of motions—is a promising approach for obtaining flexibility in devices as well as areal coverage. A team led by Liwei Lin from University of California, Berkley now apply laser-induced graphitic conversion and cutting to achieve micro-supercapacitors that can be elongated to over 380% with a functional component areal coverage of over 70%. A range of Kirigami-inspired designs are demonstrated, suggesting the concept might be applied to other flexible functional devices.